Demarcation BUMN: Between Private Laws and Public Laws - Indah Cahyani; Tatiek Sri Djatmiati (Universitas Airlangga, 2019)
The article titled “BUMN between Private Law and Public Law” aims to find the best solution for crossing the position of BUMN that meets in it two different legal regimes namely private law and public law in Indonesia. Until now it has not been found yet, the most appropriate measure to differentiate BUMN/BUMD is subject to state finance or whether it is subject to the private financial system. Law Number 17 of 2003 concerning state finance has a strong public law nuance representing Hobbes's thinking, while Law Number 19 of 2003 concerning BUMN is stronger in the spirit of private law which represents Grotius' ideas, the problem that arises, namely how to resolve the law dogmatically fairly between the two laws that contain the opposite spirit. The article uses normative legal research methods with a conceptual approach, a statutes approach and a legal case approach. This research resulted in recommendations for the use of legal philosophy as a meta theory for legal theory to be the settlement of the meeting point to find an equilibrium that fulfills a sense of justice.